Observations of the Growth and Decay of Stall Cells during Stall and Surge in an Axial Compressor - Adam R. Hickman; Scott C. Morris (International Journal of Rotating Machinery)
This research investigated unsteady events such as stall inception, stall-cell development, and surge. Stall is characterized by a decrease in overall pressure rise and nonaxisymmetric throughflow. Compressor stall can lead to surge which is characterized by quasi-axisymmetric fluctuations in mass flow and pressure. Unsteady measurements of the flow field around the compressor rotor are examined. During the stall inception process, initial disturbances were found within the rotor passage near the tip region. As the stall cell develops, blade lift and pressure ratio decrease within the stall cell and increase ahead of the stall cell. The stall inception event, stall-cell development, and stall recovery event were found to be nearly identical for stable rotating stall and surge cases. As the stall cell grows, the leading edge of the cell will rotate at a higher rate than the trailing edge in the rotor frame. The opposite occurs during stall recovery. The trailing edge of the stall cell will rotate at the approximate speed as the fully developed stall cell, while the leading edge decreases in rotational speed in the rotor frame.